A manufacturing process of solder resist dry film

By using nano reinforcement agents and low-temperature curing agents in the manufacturing process of welding-proof dry films, the problem of weak bending resistance of welding-proof dry films is solved, and efficient cooperation on rolled circuit boards is achieved, and production efficiency and product quality are improved.

CN119751954APending Publication Date: 2025-04-04GUANGDONG ZECHENG TECHNOLOGY CO., LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510196724.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-21
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The existing welding-proof dry films are not bending resistant when rolling bonding cooperation is required, making them difficult to be suitable for rolling circuit boards.

Method used

Using a manufacturing process of welding-proof dry film, a welding-proof dry film is obtained by mixing resin raw materials, nano reinforcement agents, high adhesion fillers and low-temperature curing agents in sequence to form a welding-proof insulating mixture, and uniformly coated on the surface of the polymer substrate, and then curing at low temperature under a low pressure state to obtain a welding-proof dry film with improved bending resistance.

Benefits of technology

Through the interface enhancement effect of nano reinforcement agent, the stress during bending is effectively dispersed, cracks and deformation are reduced, and the bending strength of the welding-proof dry film is improved, making it suitable for the joint work of rolled circuit boards.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751954A_ABST
    Figure CN119751954A_ABST
Patent Text Reader

Abstract

The present invention proposes a manufacturing process of a solder-proof dry film, the steps comprising: mixing a resin raw material, a nano-enhancer, a high-adhesion filler and a low-temperature curing agent in order to obtain a solder-proof insulating mixture; uniformly coating the solder-proof insulating mixture on the surface of a polymer substrate to obtain a composite matrix; placing the composite matrix in a curing device with temperature regulation and air pressure regulation, adjusting to a low-pressure state, and performing low-temperature curing to obtain a solder-proof dry film. The nano-enhancer has a very large specific surface area and can form a stronger interface bond with the resin matrix. Through this interface enhancement, the stress generated during bending can be effectively dispersed, and the occurrence of cracks and deformation can be reduced. The distribution of the nano-enhancer in the composite material not only improves the hardness of the matrix material, but also improves the load transfer capacity. When the composite material is subjected to bending stress, the nano-enhancer helps to effectively disperse the stress, thereby improving the bending strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of semiconductor packaging, and in particular relates to a manufacturing process of a solder resist dry film. Background Art

[0002] Solder mask plays a vital role in semiconductor packaging. It is mainly used to protect the surface of integrated circuit (IC) chips and circuit boards and other components used in the packaging process. Solder mask is widely used on the surface of circuit boards, especially on PCBs (printed circuit boards). It covers pads, lines and other important areas to prevent metal solder from contaminating or corroding the surface of the circuit board during the welding process. During the welding process, the solder mask can effectively isolate the non-welding area on the circuit board, prevent solder from overflowing or penetrating into the parts that should not be exposed to solder, and reduce the occurrence of short circuits. The function of the solder mask is to prevent oxidation of the copper surface caused by high-temperature welding, avoid damage caused by excessive welding, and effectively improve the quality and stability of the package.

[0003] The solder mask dry film in the related art is made of resin-based materials, and commonly used materials include epoxy resin, polyimide, etc., which show good heat resistance, chemical resistance and electrical insulation in some aspects. However, many solder mask materials (such as epoxy resin) are relatively hard after curing, lack sufficient toughness and ductility, resulting in weak bending resistance and easy breakage or cracking when bent or stretched. In order to improve the bonding efficiency and accuracy, the circuit board needs to be set in a roll to facilitate continuous bonding and transportation. The solder mask dry film with weak bending resistance is difficult to be used in bonding operations that require roll-type circuit boards. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a manufacturing process of a solder mask dry film, aiming to solve the problem that the solder mask dry film has low bending resistance under the premise of requiring roll-to-roll lamination operation.

[0005] To solve the above technical problems, the present invention is implemented as follows: the present invention proposes a manufacturing process of a solder resist dry film, the steps comprising: S1, mixing a resin raw material, a nano-reinforcement agent, a high-adhesion filler and a low-temperature curing agent in order to obtain a solder-proof insulating mixture, wherein the nano-reinforcement agent includes at least one of nano-silicate, carbon nanotubes and nano-alumina; S2, uniformly coating the solder-proof insulating mixture on the surface of the polymer substrate to obtain a composite matrix; S3, placing the composite matrix in a curing device with temperature and pressure regulation, adjusting it to a low pressure state, and performing low temperature curing to obtain a solder resist dry film.

[0006] In some embodiments of the present invention, in step S1, the resin raw material includes at least one of polyurethane acrylic resin, epoxy acrylic resin, and methyl methacrylate resin, the high adhesion filler includes at least one of surface modified silica, modified alumina, and functionalized titanium oxide, and the low-temperature curing agent includes at least one of diisocyanate curing agent, melamine formaldehyde resin, and multifunctional cross-linking agent.

[0007] In some embodiments of the present invention, step S1 comprises: S1.1. Place the resin raw material and the low-temperature curing agent in a stirring reactor with stirring and temperature regulation functions, and stir them for 10 to 15 minutes at a stirring speed of 1000 to 3000 rpm and a stirring temperature of 30 to 40°C; S1.2, adding the nano-enhancer in batches and stirring, then adding the high adhesion filler and doping the thickener to obtain a solder-proof insulating mixture with a viscosity in the range of 500-800 mPa·s; S1.3. Measure the particle dispersion in the solder-proof insulating mixture by a dynamic light scattering instrument, and stop stirring when the particle dispersion meets a preset range and the pH value of the solder-proof insulating mixture reaches 6.5-7.5.

[0008] In some embodiments of the present invention, in step S1.2, the thickener includes at least one of hydroxypropyl methylcellulose, sodium polyacrylate, and xanthan gum.

[0009] In some embodiments of the present invention, step S2 includes: S2.1. Activate the surface of the polymer substrate, place it in a spraying device, and first spray the heat-sensitive coating to form a heat-sensitive layer; S2.2, spraying the solder-proof insulating mixture onto the heat-sensitive layer to obtain a composite matrix.

[0010] In some embodiments of the present invention, in step S2.1, the heat-sensitive coating includes at least one of polyvinyl alcohol, polyacrylic acid, and polylactic acid, and the thickness of the heat-sensitive layer is 10-20 μm.

[0011] In some embodiments of the present invention, step S3 includes: S3.1. Preheat the ambient temperature in the curing device to 80~90℃; S3.2, placing the composite substrate in a curing device, adjusting the air pressure to 500-600 mbar, raising the temperature to 90-100°C, and using a reflection interference microscope to determine whether the solder-resistant insulating mixture on the composite substrate has been cured, and obtaining a solder-resistant dry film after curing.

[0012] In some embodiments of the present invention, the step of judging whether the solder resist insulating mixture on the composite substrate has completed curing by using a reflection interference microscope comprises: Obtain standard interference fringes of a reference sample of known thickness and without bubbles; Obtaining coating interference fringes of the solder-resistant insulating mixture on the composite substrate; Comparing the standard interference fringes with the coating interference fringes and obtaining a similarity ratio; If the same rate is greater than or equal to the preset judgment value, the solder-proof insulating mixture on the composite substrate is completely cured; If the same rate is less than the preset judgment value, the solder resist insulating mixture on the composite substrate has not been completely cured.

[0013] Compared with the prior art, the manufacturing process of the solder mask dry film in the present invention has the following beneficial effects: Nano-reinforcers have a very large specific surface area and can form a stronger interface bond with the resin matrix. Through this interface reinforcement, the stress generated during bending can be effectively dispersed, reducing the occurrence of cracks and deformation. The distribution of nano-reinforcers in the composite material not only improves the hardness of the matrix material, but also improves the load transfer capacity. When the composite material is subjected to bending stress, the nano-reinforcers help to effectively disperse the stress, thereby improving the bending strength. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 It is a schematic flow chart of a manufacturing process of a solder mask dry film in one embodiment of the present invention. DETAILED DESCRIPTION

[0015] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0016] Please refer to Figure 1 The present invention provides a manufacturing process of a solder mask dry film, the steps comprising: S1. Mixing a resin raw material, a nano-reinforcement agent, a high-adhesion filler and a low-temperature curing agent in order to obtain a solder-proof insulating mixture, wherein the nano-reinforcement agent includes at least one of nano-silicate, carbon nanotube and nano-alumina.

[0017] Silicate nanomaterials have high rigidity and strength. When added to a resin matrix, they can significantly improve the material's bending resistance. Their nanoscale size and high surface area enable them to form a stronger interface bond with the resin matrix, thereby enhancing the overall rigidity of the composite material. When the matrix is ​​subjected to bending stress, the silicate particles can share the stress and reduce deformation during bending.

[0018] Carbon nanotubes have ultra-high mechanical strength and elastic modulus. When added to resin, they can significantly improve the bending rigidity of the resin. Carbon nanotubes form a network structure in the resin, which can significantly improve the bending resistance of the material by providing a reinforced skeleton structure and reduce the breakage or yielding of the material during bending.

[0019] Nano-alumina has high hardness and excellent wear resistance. After being added to the composite material, it can improve the bending rigidity of the resin and enhance the resistance of the material under external forces. Under bending load, alumina can effectively disperse stress and reduce local stress concentration, thereby improving bending strength.

[0020] Nano-reinforcers have a very large specific surface area and can form a stronger interface bond with the resin matrix. Through this interface reinforcement, the stress generated during bending can be effectively dispersed, reducing the occurrence of cracks and deformation. The distribution of nano-reinforcers in the composite material not only improves the hardness of the matrix material, but also improves the load transfer capacity. When the composite material is subjected to bending stress, the nano-reinforcers help to effectively disperse the stress, thereby improving the bending strength.

[0021] As a matrix material, resin provides the basic strength and elasticity of the composite material. Commonly used resins such as polyurethane acrylic resin and epoxy acrylic resin have good adhesion and toughness. With the help of nano-reinforcement agents, they can maintain a certain degree of flexibility and ductility to prevent the material from cracking when bent.

[0022] Low-temperature curing agents can effectively enhance the cross-linking structure of the resin during the curing process, improving the overall stability and strength of the material. The cured material can maintain good mechanical properties and reduce deformation when subjected to bending loads.

[0023] In one embodiment, step S1 includes: S1.1. Place the resin raw material and the low-temperature curing agent in a stirring reactor with stirring and temperature adjustment functions, and stir them. The stirring time is 10-15 min, for example, 10 min, 13 min, 15 min. The stirring speed is 1000-3000 rpm, for example, 1000 rpm, 2000 rpm, 3000 rpm. The stirring temperature is 30-40°C, for example, 30°C, 35°C, 50°C.

[0024] In this step, the stirring of the resin raw material and the low-temperature curing agent can ensure that they are fully and evenly distributed in the solder-proof insulation mixture, providing a good foundation for subsequent reactions. Through stirring, the molecules of the resin raw material and the curing agent can be evenly mixed to avoid incomplete reaction between the curing agent and the resin raw material or uneven local curing. The role of the temperature regulation function is to control the viscosity and reaction rate of the solder-proof insulation mixture. The temperature of 30~40℃ helps the reaction between the resin raw material and the curing agent to be more stable and efficient, while avoiding too fast reaction at too high a temperature, resulting in unstable or uneven curing. Precise control of the stirring time and stirring speed helps to maintain the fluidity of the system, prevent the precipitation of large particles, and ensure the stability of the system.

[0025] The resin raw material includes at least one of polyurethane acrylic resin, epoxy acrylic resin, and methyl methacrylate resin, the high adhesion filler includes at least one of surface modified silica, modified alumina, and functionalized titanium oxide, and the low-temperature curing agent includes at least one of diisocyanate curing agent, melamine formaldehyde resin, and multifunctional cross-linking agent.

[0026] S1.2, adding the nano-enhancer in batches and stirring, then adding the high adhesion filler and doping the thickener to obtain a solder-proof insulating mixture with a viscosity in the range of 500-800 mPa·s.

[0027] Nano-reinforcements such as nano-silicates, carbon nanotubes, and nano-alumina can significantly improve the mechanical properties of composite materials (such as flexural strength, impact strength, etc.). These nanomaterials have a very high specific surface area and can provide additional support in the resin matrix, improving the rigidity and strength of the composite material. High adhesion fillers (such as surface-modified silica, modified alumina, etc.) can enhance the bonding between the resin and the substrate, ensure good adhesion of the coated material, and prevent peeling or cracking caused by stress. The addition of thickeners keeps the viscosity of the solder mask insulation mixture stable in the range of 500~800mPa·s. This viscosity range helps to evenly coat the solder mask insulation mixture, avoid insufficient or excessive fluidity of the material during the coating process, and ensure uniformity and operability.

[0028] The thickener includes at least one of hydroxypropyl methylcellulose, sodium polyacrylate and xanthan gum.

[0029] S1.3. Measure the particle dispersion in the solder mask insulation mixture by a dynamic light scattering instrument. Stop stirring when the particle dispersion meets the preset range and the pH value of the solder mask insulation mixture reaches 6.5-7.5.

[0030] Dynamic light scattering can accurately measure the dispersion state of nano-enhancements in solder mask insulation mixtures. By measuring the dispersion of particles, the uniform distribution of nano-enhancements can be ensured. If the particle dispersion is not good, it may lead to unstable material performance or form large particle agglomerations, affecting mechanical properties and processing. Therefore, measuring the particle dispersion and ensuring it is within a preset range helps to ensure the uniformity, stability and subsequent performance of the composite material.

[0031] By controlling the pH value of the solder mask insulation mixture between 6.5 and 7.5, it can be ensured that the chemical reaction between the resin raw material, curing agent and filler is carried out in a suitable acid-base environment. Too high or too low pH value will affect the curing effect of the resin and the dispersion of the filler, resulting in adverse reactions or reducing the performance of the composite material. When the particle dispersion meets the requirements and the pH value is in the ideal range, the stirring can be stopped. This ensures that the preparation process of the solder mask insulation mixture is completed in the best state, laying the foundation for the subsequent coating steps.

[0032] S2. The solder-proof insulating mixture is uniformly coated on the surface of the polymer substrate to obtain a composite matrix.

[0033] Through the coating operation, it is possible to ensure that the thickness of the solder mask is uniform and free of defects such as bubbles and cracks, thereby improving the quality of the solder mask dry film and avoiding problems such as uneven welding or peeling in subsequent use. The solder mask insulation mixture (solder mask) coated on the surface of the substrate forms a tight bond with the polymer substrate, which helps to improve the structural stability of the entire composite matrix, enhance its ability to resist mechanical stress and thermal stress, and avoid material shedding due to external force or temperature changes.

[0034] Adding nano-enhancers (such as nano-silicates, carbon nanotubes, and nano-alumina) to the solder-proof insulation mixture can improve the bending resistance, heat resistance, impact resistance and other properties of the solder-proof dry film after coating. In addition, high-adhesion fillers can improve the bonding between the film layer and the substrate, making the adhesion performance of the coating more stable. The solder-proof layer formed on the surface of the substrate not only plays a protective role, but also provides electrical insulation, solder resistance, corrosion resistance, and oxidation resistance, which is very important for protecting electronic components and electrical connections on circuit boards.

[0035] In one embodiment, step S2 includes: S2.1. Activate the surface of the polymer substrate, place it in a spraying device, and first spray a thermosensitive coating to form a thermosensitive layer; the thermosensitive coating includes at least one of polyvinyl alcohol, polyacrylic acid, and polylactic acid, and the thickness of the thermosensitive layer is 10-20 μm.

[0036] The purpose of activating the surface of the polymer substrate is to increase its surface energy and reactivity, making it easier to chemically react or physically adsorb with the subsequently sprayed thermally sensitive coating or solder resist insulation mixture, thereby enhancing the adhesion of the subsequent coating to the substrate.

[0037] Before activation treatment, the surface of the polymer substrate needs to be cleaned to remove oil, dust and other impurities on the surface to ensure that the surface is clean so that subsequent treatment can be carried out more effectively. The surface of the polymer substrate can be soaked or wiped with an appropriate solvent (such as isopropyl alcohol, ethanol or deionized water) to dissolve and remove grease and other surface contaminants to ensure a clean surface.

[0038] Place the cleaned substrate in a dry environment and dry it with air flow or in an oven. Completely remove the solvent or moisture on the surface to avoid affecting the subsequent coating process.

[0039] Use sandpaper to gently polish the surface of the polymer substrate, or use mechanical methods such as rotating brushes and sandblasting to roughen the surface. Enhance the micro-roughness of the substrate surface to provide a larger contact area for subsequent coatings and improve the adhesion between the coating and the substrate.

[0040] The substrate is placed in a plasma reaction chamber and the polymer surface is treated at low temperature by ionized gas (such as argon, oxygen, etc.). Plasma can effectively destroy the molecular chain structure on the polymer surface and generate polar groups (such as carboxyl, amino, hydroxyl, etc.), thereby increasing the hydrophilicity and reactivity of the polymer surface and promoting adhesion with subsequent coatings.

[0041] Expose the polymer substrate to ultraviolet (UV) radiation, usually using a low-pressure mercury lamp or UV laser. UV radiation can induce changes in the chemical structure of the polymer surface, generate free radicals, and increase surface activity.

[0042] Use acid (such as concentrated sulfuric acid, hydrofluoric acid or phosphoric acid) to soak the surface of the polymer substrate, usually for 5 to 15 minutes. Acidic treatment can produce an oxidation reaction on the surface of the substrate, remove pollutants and introduce polar groups such as surface carboxyl and hydroxyl groups, thereby improving surface activity and coating adhesion. Alternatively, use sodium hydroxide (NaOH) or ammonia water to treat the surface of the polymer substrate for 5 to 10 minutes. Alkaline treatment can destroy some weak bonds on the polymer surface, generate a more hydrophilic surface, and improve coating adhesion.

[0043] Alternatively, the surface of the polymer substrate is treated with oxidants such as hydrogen peroxide or ozone, often in combination with high temperature treatment. Oxidants can trigger surface oxidation reactions, introduce polar groups such as carboxyl and hydroxyl groups, improve the hydrophilicity and chemical reactivity of the substrate surface, and enhance the bonding strength with the coating.

[0044] Thermal coatings have good thermal sensitivity, that is, they can undergo physical or chemical changes at a specific temperature. For example, polyvinyl alcohol can dissolve or soften at a lower temperature, while polyacrylic acid has good adhesion and can enhance the bonding strength with the substrate at a certain temperature. The thermal layer formed after spraying thermal coatings can protect the surface of the substrate from environmental pollution or other chemicals before the solder mask insulation mixture is applied, especially to avoid direct contact with the resin solder mask insulation mixture during the spraying process. The molecular structure of thermal coatings can soften or dissolve during heating to form a layer of film with good adhesion, which enhances the bonding strength between the solder mask insulation mixture and the substrate, thereby improving the bonding strength and anti-peeling performance of the composite matrix. The thickness of the thermal layer is set at 10~20μm, which can accurately control the coating thickness, ensure the uniformity and consistency of the solder mask dry film, and avoid unstable performance caused by too thick or too thin coatings.

[0045] Polyvinyl alcohol has good water solubility, is easy to apply and dissolves easily at low temperatures, and is suitable for forming temperature-sensitive protective layers. Polyacrylic acid has good adhesion and can enhance the adhesion to the polymer substrate after heating, and is particularly suitable for improving the stability and performance of heat-sensitive coatings. Polylactic acid has good thermoplasticity when heated, and can form a strong film structure under certain heat treatment, which helps to improve the stability and heat resistance of the solder mask.

[0046] S2.2, spray the solder-proof insulating mixture onto the heat-sensitive layer to obtain a composite matrix.

[0047] By spraying the solder resist and insulating mixture on the sprayed thermal layer, a complete solder resist dry film structure can be obtained. The components in the solder resist and insulating mixture react physically or chemically with the thermal layer to ensure the adhesion, toughness and other functional properties of the solder resist film. By spraying, it is ensured that the solder resist and insulating mixture can be evenly covered on the thermal layer to form a composite matrix with uniform thickness and structure, thereby providing comprehensive functions such as electrical insulation, solder protection, and corrosion resistance. During the spraying process, the nano-enhancer in the solder resist and insulating mixture can be evenly distributed in the coating, thereby enhancing the mechanical properties of the solder resist film, especially in terms of bending resistance, high temperature resistance and impact resistance. The high adhesion filler in the solder resist and insulating mixture can further enhance the adhesion between the solder resist layer and the substrate, making the composite matrix more durable and anti-aging.

[0048] S3, placing the composite substrate in a curing device with temperature and pressure regulation, adjusting it to a low pressure state, and performing low temperature curing to obtain a solder resist dry film.

[0049] In the manufacturing process of solder mask dry film, the substrate is usually some kind of plastic or polymer material, which may be sensitive to high temperature. Excessively high curing temperature can cause deformation, degradation or loss of performance of the substrate. Therefore, choosing low temperature curing can effectively avoid thermal damage to the substrate and ensure the stability of its morphology and performance. During the coating process, the purpose of the thermal coating is to dissolve or soften at high temperature to enhance the bonding between the solder mask insulation mixture and the substrate. If the curing temperature is too high, it may cause the thermal coating to react or be damaged prematurely before coating, affecting the adhesion and solder mask effect of the film. Low temperature curing can ensure that the thermal coating reacts correctly when the temperature rises, while providing enough time for the solder mask insulation mixture to combine with the substrate. In the formula, nano-enhancers such as nano-silicates, carbon nanotubes, and nano-alumina are used. They usually have good thermal stability and can maintain their performance at lower temperatures. The role of these enhancers is to improve the strength, bending resistance and heat resistance of the solder mask, so the curing temperature does not need to be too high to avoid performance changes of these nano-enhancers. The low temperature curing process can be completed relatively slowly, so that the coating remains uniform during the curing process. Too high a temperature may result in rapid curing, which may lead to uneven film layers, the generation of bubbles or poor interlayer adhesion. Low temperature curing can better control the curing process and ensure the quality of the film layer.

[0050] In the formulation, the use of low-temperature curing agents such as diisocyanate curing agents, melamine formaldehyde resins, etc. usually requires lower temperatures to control their curing reactions. Too high a temperature may cause these curing agents to react too quickly or excessively, affecting the uniformity and performance of the final solder mask. These side reactions can be effectively avoided by controlling the curing temperature within a lower range. Low-temperature curing can ensure that the components in the solder mask insulation mixture, such as nano-reinforcements, fillers, and resin components, are cross-linked at an appropriate speed and manner, thereby ensuring that the formed film has good flexibility and anti-bending properties. Too high a curing temperature may cause too fast curing, affect the arrangement of the molecular chains, and reduce the anti-bending properties of the film.

[0051] In one embodiment, step S3 includes: S3.1. Preheat the ambient temperature in the curing device to 80-90°C, for example, 80°C, 85°C, or 90°C.

[0052] Preheating the curing device to 80~90℃ can reduce temperature fluctuations during the curing process and ensure a more uniform curing process. This can prevent thermal stress in the composite matrix due to excessive temperature differences during the curing process, resulting in deformation of the substrate or cracks in the film layer. By heating the curing device to a temperature close to the target curing temperature in advance, the subsequent heating time can be reduced and the efficiency of the process can be improved. For low-temperature curing processes, proper preheating can help start the curing reaction faster while avoiding the negative effects of excessive temperatures on the substrate and coating. Preheating stabilizes the curing equipment within an ideal temperature range, ensures uniform distribution of internal temperature, avoids local overheating or overcooling, and ensures the stability of the entire curing process.

[0053] S3.2. Place the composite substrate in a curing device, adjust the air pressure to 500-600 mbar, for example, 500 mbar, 550 mbar, 600 mbar, raise the temperature to 90-100°C, for example, 90°C, 95°C, 100°C, and use a reflection interference microscope to determine whether the solder-resistant insulating mixture on the composite substrate has been cured. When the curing is completed, a solder-resistant dry film is obtained.

[0054] Curing under low pressure helps remove bubbles in the substrate and film layer, which usually affect the uniformity and strength of the solder mask. By reducing the pressure, the uncured components in the solder mask insulation mixture can be quickly volatilized or removed from the film layer, reducing the formation of bubbles and holes. Low pressure conditions help to increase the density of the coating, promote uniform curing of the solder mask insulation mixture, reduce defects inside the film layer, and thus enhance the mechanical strength and protective properties of the solder mask.

[0055] During the curing process, the temperature is raised to 90~100℃ to ensure that the low-temperature curing agent reacts fully and evenly. This temperature range can promote the cross-linking of the resin and avoid excessively high temperatures that damage the substrate or cause other performance problems. During the curing process, the dual control of temperature and pressure ensures that the solder mask insulation mixture can complete the curing reaction smoothly and avoid adverse changes in the film layer due to excessively high or uneven temperatures.

[0056] Using a reflective interference microscope to monitor the curing state of the solder mask insulation mixture in real time can accurately determine whether the film layer has been cured. By analyzing the interference phenomenon of light, the reflective interference microscope can determine the changes in the optical thickness and reflectivity of the film surface, which are closely related to the curing process. Through the feedback data from the microscope, the operator can accurately control the curing time to avoid over-curing or under-curing. This detection method can efficiently and accurately determine the completion of curing, thereby reducing human errors in the production process and improving production efficiency and product quality. The reflective interference microscope can detect the integrity of the film layer, especially the thickness, surface flatness and uniformity of the film layer. During the curing process, any uncured area will appear as a different interference pattern under the microscope, so problems can be discovered and corrected in time.

[0057] Specifically, the step of judging whether the solder resist insulating mixture on the composite substrate has completed curing by using a reflection interference microscope includes: Step 321: Obtain standard interference fringes of a reference sample with known thickness and no bubbles.

[0058] Obtain standard interference fringes of a reference sample with no bubbles and known thickness to provide an accurate benchmark for subsequent comparison. The interference fringes of the standard sample are known and represent the state of a fully cured and defect-free coating. Therefore, it provides a benchmark for comparison to ensure the accuracy and reliability of the inspection process. The reference sample without bubbles eliminates the interference error caused by bubbles, making the measurement results more accurate. This is crucial for the quality control of the coating to ensure that there will be no misjudgment due to the presence of bubbles in the actual inspection.

[0059] Step 322: Obtain coating interference fringes of the solder resist and insulating mixture on the composite substrate.

[0060] Obtaining interference fringes of coatings on composite substrates allows real-time monitoring of the curing state of the coating. At different stages of curing of the coating, the shape, spacing, and color of the interference fringes will change. By observing these changes, it is possible to quickly determine whether the coating has reached the desired degree of cure. The changes in the interference fringes not only reflect the curing state, but also provide an accurate measurement of the thickness and uniformity of the coating. This helps determine if the coating has defects, such as uneven curing or areas that are not fully cured.

[0061] Step 323: Compare the standard interference fringes and the coating interference fringes and obtain the same ratio.

[0062] Comparing the standard interference fringes with the coating interference fringes can quantify the curing process. The calculation method of the same rate makes the judgment of the curing process more objective and scientific. Through numerical comparison, the error of human judgment is reduced and the accuracy of judgment is ensured. Using quantitative same rate to evaluate the curing process avoids the subjectivity of relying solely on visual observation, and can provide production personnel with clear indication of the curing status, reducing misjudgment or delays.

[0063] Before comparing the fringes, the images are denoised to remove background noise and unnecessary interference. The standard and coating interference fringes are also aligned to ensure they are in the same position for direct comparison.

[0064] The calculation method of the same rate includes the following: (1) Cross-correlation method: The similarity between the standard interference fringe image and the coating interference fringe image is determined by calculating the cross-correlation coefficient between them. The cross-correlation coefficient is a commonly used image similarity measurement method, and its value range is usually between -1 and 1. The closer the value is to 1, the more similar the two images are.

[0065] The standard interference fringes and coating interference fringes are normalized.

[0066] Calculate the cross-correlation coefficient between them: ,in, and are the pixel values ​​of the standard interference fringes and the coating interference fringes, is the pixel coordinate, and C is the cross-correlation coefficient.

[0067] (2) Normalized mean square error, which measures the difference between the standard interference fringes and the coating interference fringes by calculating the mean square error between the two. The smaller the error, the higher the similarity between the two.

[0068] Perform differential processing on the standard interference fringe and coating interference fringe images and calculate the mean square error ,in, and is the pixel value of the standard and coating interference fringes, is the total number of pixels, and MSE is normalized to the same rate ,in, It is the maximum possible mean square error value of the image. The smaller the NMSE, the higher the similarity rate, which means the higher the degree of curing completion.

[0069] If the same rate is greater than or equal to the preset judgment value, the solder resist and insulation mixture on the composite substrate is completely cured; If the same rate is less than the preset judgment value, the solder resist insulation mixture on the composite substrate has not been cured. When incomplete curing is detected, the operator can adjust the process parameters such as curing temperature, time or air pressure based on this feedback to ensure that the coating achieves the expected curing effect and avoid problems such as poor film performance and poor adhesion caused by insufficient curing.

[0070] The preset judgment value can be 0.8~0.9. The closer to the preset judgment value, the closer the curing state is to the standard interference fringes, that is, the higher the degree of curing. In this way, it is possible to quantitatively evaluate whether the coating on the composite substrate has reached a fully cured state, avoiding the error of subjective judgment and providing a more reliable and accurate means of curing monitoring. This method can not only improve production efficiency, but also ensure the quality consistency of the final product, especially in the environment of large-scale production and strict quality control, and has important application value.

[0071] The uniformity of the solder-resistant insulating layer composed of the solder-resistant insulating mixture in the solder-resistant dry film prepared through the above steps can reach + / - 2 um.

[0072] The solder mask dry film is used for laminating chip substrates or circuit layers. In the vacuum laminating process, it effectively reduces cracks and bubbles generated during chip laminating. With traditional screen printing, single-sided printing, pre-baking, single-sided printing, and post-baking (there is also a waiting time after printing), which requires a lot of manpower to operate. The use of solder mask dry film can greatly reduce the production process. It only requires vacuum double-sided lamination and post-baking to complete the laminating operation. The production efficiency is improved, and the original 30 hours is shortened to 3 hours, and the production manpower is reduced by 75% (compared with traditional screen printing).

[0073] At the same time, the use of solder mask dry film for lamination operations is completely solvent-free, eliminating the smell of solvents produced by adjusting inks at the work site. In the closed space of the vacuum pressing equipment, there is no external environmental interference and pollution is reduced, which helps to solve the uncontrollable problems existing in traditional processes and promote the integrated circuit packaging industry to develop in a more efficient and higher-quality direction.

[0074] The specific structures and usage principles of the devices, equipment or other elements such as sensors used in the specification of the present invention are well known to those skilled in the art and will not be described in detail here.

[0075] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A process for manufacturing a solder mask dry film, characterized in that the steps include: S1, mixing a resin raw material, a nano-reinforcement agent, a high-adhesion filler and a low-temperature curing agent in order to obtain a solder-proof insulating mixture, wherein the nano-reinforcement agent includes at least one of nano-silicate, carbon nanotubes and nano-alumina; S2, uniformly coating the solder-proof insulating mixture on the surface of the polymer substrate to obtain a composite matrix; S3, placing the composite matrix in a curing device with temperature and pressure regulation, adjusting it to a low pressure state, and performing low temperature curing to obtain a solder resist dry film.

2. The manufacturing process of the solder mask dry film according to claim 1, characterized in that: In step S1, the resin raw material includes at least one of polyurethane acrylic resin, epoxy acrylic resin, and methyl methacrylate resin, the high adhesion filler includes at least one of surface modified silica, modified alumina, and functionalized titanium oxide, and the low-temperature curing agent includes at least one of diisocyanate curing agent, melamine formaldehyde resin, and multifunctional cross-linking agent.

3. The manufacturing process of the solder mask dry film according to claim 1, characterized in that: The step S1 comprises: S1.

1. Place the resin raw material and the low-temperature curing agent in a stirring reactor with stirring and temperature regulation functions, and stir them for 10 to 15 minutes at a stirring speed of 1000 to 3000 rpm and a stirring temperature of 30 to 40°C; S1.2, adding the nano-enhancer in batches and stirring, then adding the high adhesion filler and doping the thickener to obtain a solder-proof insulating mixture with a viscosity in the range of 500-800 mPa·s; S1.

3. Measure the particle dispersion in the solder-proof insulating mixture by a dynamic light scattering instrument, and stop stirring when the particle dispersion meets a preset range and the pH value of the solder-proof insulating mixture reaches 6.5-7.

5.

4. The manufacturing process of the solder mask dry film according to claim 3, characterized in that: In the step S1.2, the thickener includes at least one of hydroxypropyl methylcellulose, sodium polyacrylate, and xanthan gum.

5. The manufacturing process of the solder mask dry film according to claim 1, characterized in that: The step S2 comprises: S2.

1. Activate the surface of the polymer substrate, place it in a spraying device, and first spray the heat-sensitive coating to form a heat-sensitive layer; S2.2, spraying the solder-proof insulating mixture onto the heat-sensitive layer to obtain a composite matrix.

6. The manufacturing process of the solder mask dry film according to claim 5, characterized in that: In the step S2.1, the heat-sensitive coating includes at least one of polyvinyl alcohol, polyacrylic acid, and polylactic acid, and the thickness of the heat-sensitive layer is 10-20 μm.

7. The manufacturing process of the solder mask dry film according to claim 1, characterized in that: The step S3 comprises: S3.

1. Preheat the ambient temperature in the curing device to 80~90℃; S3.2, placing the composite substrate in a curing device, adjusting the air pressure to 500-600 mbar, raising the temperature to 90-100°C, and using a reflection interference microscope to determine whether the solder-resistant insulating mixture on the composite substrate has been cured, and obtaining a solder-resistant dry film after curing.

8. The manufacturing process of the solder mask dry film according to claim 7, characterized in that: The step of judging whether the solder resist insulating mixture on the composite substrate has been cured by using a reflection interference microscope comprises: Obtain standard interference fringes of a reference sample of known thickness and without bubbles; Obtaining coating interference fringes of the solder-resistant insulating mixture on the composite substrate; Comparing the standard interference fringes with the coating interference fringes and obtaining a similarity ratio; If the same rate is greater than or equal to the preset judgment value, the solder-proof insulating mixture on the composite substrate is completely cured; If the same rate is less than the preset judgment value, the solder resist insulating mixture on the composite substrate has not been completely cured.